2020
DOI: 10.1371/journal.pone.0228891
|View full text |Cite
|
Sign up to set email alerts
|

Calorie and nutrient trends in large U.S. chain restaurants, 2012-2018

Abstract: IntroductionLarge chain restaurants reduced calories in their newly-introduced menu items from 2012 to 2015. The objective of this study was to provide updated calorie trends through 2018 and examine trends in the macronutrient composition of menu items across this time period. OPEN ACCESS Citation: Bleich SN, Soto MJ, Dunn CG, Moran AJ, Block JP (2020) Calorie and nutrient trends in large U.S. chain restaurants, 2012-2018. PLoS ONE 15 (2): e0228891. https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Positive effects: Bleich et al (2020) reported the results of a longitudinal study (2012-2018) that examined nutrient trends for 28,238 food and beverage menu items from 28,238 US chain restaurants. The results found less calories in food items, and less calories and saturated fat in beverages, with results attributed to the US national menu labeling law [51]. Similar results were noted for six US studies that documented a significant decline in calories of certain items [19,[48][49][50]53,55].…”
Section: Changes In the Nutritional Composition By Nutrients Of Concernsupporting
confidence: 80%
See 3 more Smart Citations
“…Positive effects: Bleich et al (2020) reported the results of a longitudinal study (2012-2018) that examined nutrient trends for 28,238 food and beverage menu items from 28,238 US chain restaurants. The results found less calories in food items, and less calories and saturated fat in beverages, with results attributed to the US national menu labeling law [51]. Similar results were noted for six US studies that documented a significant decline in calories of certain items [19,[48][49][50]53,55].…”
Section: Changes In the Nutritional Composition By Nutrients Of Concernsupporting
confidence: 80%
“…The small number of studies that assessed other nutrients of concern (i.e., saturated fats, trans fats, sodium, and added sugars) [16,51,56,57,59] rather than just energy might be the consequence of policies limiting the regulation to reporting the energy content. All 11 countries that have implemented restaurant menu labeling policies require the disclosure of energy (i.e., calories or kilojoules).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Last, we assess whether our data may be confounded by direct effects of the calorie labeling requirement on the formulation of menu items because our data postdates the announcement of the requirement in the 2010 ACA. Prior studies have documented reductions in calories with MenuStat data [60,71]. To assess this possibility, we sample menu items and compare calorie counts before and after the enactment of the labeling requirement.…”
Section: Robustnessmentioning
confidence: 99%